Petroselinum crispumhas antioxidant properties, protects against DNA damage and inhibits proliferation and migration of cancer cells - Tang, Esther Lai-Har; Rajarajeswaran, Jayakumar; Fung, Shin Yee; Kanthimathi, M S Subramaniam (Wiley, 2015)
BACKGROUND: Petroselinum crispum (English parsley) is a common herb of the Apiaceae family that is cultivated throughout the world and is widely used as a seasoning condiment. Studies have shown its potential as a medicinal herb. In this study, P. crispum leaf and stem extracts were evaluated for their antioxidant properties, protection against DNA damage in normal 3T3-L1 cells, and the inhibition of proliferation and migration of the MCF-7 cells. RESULTS: The dichloromethane extract of P. crispum exhibited the highest phenolic content (42.31 ± 0.50 mg GAE g-1) and ferric reducing ability (0.360 ± 0.009 mmol g-1) of the various extractions performed. The extract showed DPPH radical scavenging activity with an IC50 value of 3310.0 ± 80.5 μg mL-1. Mouse fibroblasts (3T3-L1) pre-treated with 400 μg mL-1 of the extract showed 50.9% protection against H2O2-induced DNA damage, suggesting its potential in cancer prevention. The extract (300 μg mL-1) inhibited H2O2-induced MCF-7 cell migration by 41% ± 4%. As cell migration is necessary for metastasis of cancer cells, inhibition of migration is an indication of protection against metastasis. CONCLUSION: Petroselinum crispum has health-promoting properties with the potential to prevent oxidative stress-related diseases and can be developed into functional food.